Are Problems During Pregnancy a Predictor of Childbirth in The Hospital?: Determinants Analysis of Hospital Childbirth in Urban Poor Communities in Indonesia - Ratna Dwi Wulandari1 , Agung Dwi Laksono2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Although hospital services were available, urban poor people often have limited access to hospitals whenneeded. This study was conducted to analyze the determinants of childbirth in a hospital in urban poorwomen in Indonesia. The study uses raw data from the 2017 IDHS. With stratification and multistagerandom sampling, 7,891 women aged 15-49 years old in urban poor communities with live births in the last5 years were sampled. Data were analyzed using a Binary Logistic Regression test. The results of the studyfound that “problems during pregnancy” was not proven as a determinant of the hospital use for deliveryin urban poor women in Indonesia. Age was proven to be one of the determinants, while in the educationlevel category, urban poor women with tertiary education were 2.506 times more likely to use hospitalsfor delivery than urban poor women who were not in school. Parity was significantly proven as one ofthe determinants that influence the use of hospitals for delivery in urban poor women in Indonesia. Urbanpoor women who were covered by health insurance have 1.933 times more possibility of utilizing hospitalfor delivery than those who do not have health insurance. It could be concluded that the “problem duringpregnancy” variable was not a predictor of the hospital use for childbirth in the urban poor communityin Indonesia. The determinants or variables that influence, on the hospital use for childbirth were age,education, parity, and health insurance.